The Cambridge companion to Alexander the Great - Ogden, Daniel (Cambridge Companions to the Ancient World Series, 2024)
A lucid introduction to the life and career of one of the most significant figures in world history. A geographically articulated biography is followed by studies of the key themes of his campaign and analyses of ways in which the king's image was presented and manipulated in antiquity itself.